2018
DOI: 10.3991/ijet.v13i01.7513
|View full text |Cite|
|
Sign up to set email alerts
|

Article retracted.

Abstract: Abstract-Effective college English learning has long been overwhelmed by the focus on effective teaching in the traditional classroom teaching model. This paper first discusses the essential elements in effective English learning environment, deconstructs and reconstructs college English classroom by integrating Small Private Course (abbreviated as SPOC hereafter), mobile learning and social communication into classroom teaching and learning. It is concluded that the SPOC-based flipped classroom of college Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
0
13
0
2
Order By: Relevance
“…To sum up the research we identified and enumerated most of advantages and disadvantages of online educational mode operating within the ICT-based university environment from the point of view of both teachers and students (Reid, 2002;Sampson, 2003;Aoki, 2010Aoki, , 2012Bonk et al, 2015;Kaplan & Haenlein, 2016;Ainoutdinova et al, 2017;Zhang et al, 2018). The provided analysis and study allowed us to systematize the theory and practice of the process of online courses employment at university level, (Khan, 2005;Downes, 2006;Cormier & Siemens, 2010;Cormier & Stewart, 2011;Hollands & Tirthali, 2014;Bonk et al, 2015;Kaplan & Haenlein, 2016;Ainoutdinova & Ainoutdinova, 2017;Zhang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To sum up the research we identified and enumerated most of advantages and disadvantages of online educational mode operating within the ICT-based university environment from the point of view of both teachers and students (Reid, 2002;Sampson, 2003;Aoki, 2010Aoki, , 2012Bonk et al, 2015;Kaplan & Haenlein, 2016;Ainoutdinova et al, 2017;Zhang et al, 2018). The provided analysis and study allowed us to systematize the theory and practice of the process of online courses employment at university level, (Khan, 2005;Downes, 2006;Cormier & Siemens, 2010;Cormier & Stewart, 2011;Hollands & Tirthali, 2014;Bonk et al, 2015;Kaplan & Haenlein, 2016;Ainoutdinova & Ainoutdinova, 2017;Zhang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Within this timeframe the participants are free to choose their pace of study (Hollands & Thirtalli, 2014). The relative clarity of this definition of MOOC is immediately inhibited by the contrast between cMOOCs and xMOOCs (Zhang, Zhang, & Jin, 2018). https://dx.doi.org/10.15405/epsbs.2018.09.41 Corresponding Author: Irina N. Ainoutdinova Selection and peer-review under…”
Section: Specific Types Of Distance Learning Options Conducted Onlinementioning
confidence: 99%
See 2 more Smart Citations
“…As Inverted Classroom (Erwen, Wenming, & Chengxing, 2018;Rossi, 2014), têm como objetivo dinamizar, em dois estágios, os métodos que apresentam resultados significativos para a aprendizagem. No início, os estudantes recolhem informações para depois as assimilarem, sempre com a mediação do Professor, que tem como missão ajudar os estudantes a adquirirem mais responsabilidade e uma autonomia progressiva, assumindo o papel de facilitador do processo de aprendizagem (Erwen, Wenming, & Chengxing, 2018; Fidalgo-Blanco, Sein-Echaluce, & Garcia-Peñalvo, 2020; Rossi, 2014).…”
Section: Metodologias Ativasunclassified